2021
DOI: 10.3390/pharmaceutics13091518
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Calcium-Silicate Nanoparticles Loaded with Low-Dose Triton-100+Ag+ to Achieve Both Enhanced Antibacterial Properties and Low Cytotoxicity for Dentin Disinfection of Human Teeth

Abstract: Mesoporous calcium-silicate nanoparticles (MCSNs) are excellent biomaterials for controlled drug delivery and mineralization induction. In this study, MCSNs were loaded with low-dose silver ion (Ag+) and Triton X-100 (TX-100) as the M-AgTX to achieve both enhanced antibacterial properties and low cytotoxicity for dentin disinfection. The physicochemical property, biocompatibility, infiltration ability into dentinal tubules, anti-bacterial ability against both planktonic Enterococcusfaecalis (E. faecalis) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Some studies utilized mesoporous calcium-silicate NPs loaded with low-dose Ag ions, and Triton X-100 was used for the controlled delivery of AgNPs (M-AgTx). These particles inactivated a 28-day E. faecalis biofilm [ 33 ]. Likewise, M-AgTx showed excellent antibacterial ability against E. faecalis and high substantivity on dentin [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies utilized mesoporous calcium-silicate NPs loaded with low-dose Ag ions, and Triton X-100 was used for the controlled delivery of AgNPs (M-AgTx). These particles inactivated a 28-day E. faecalis biofilm [ 33 ]. Likewise, M-AgTx showed excellent antibacterial ability against E. faecalis and high substantivity on dentin [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…About 16 studies evaluated the antibacterial efcacy of AgNPs as an intracanal medicament [1,3,4,9,10,19,[21][22][23][24][25][26][27][28][29][30]. Two studies analyzed the crown discoloration caused by AgNPs [20,36], three reported the methods of their synthesis [12,31,32], and three reported recent advances in AgNPs as intracanal medicaments [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that existing studies primarily use PBNPs with 100- to 200-nm sizes for tumor treatment, but the smaller nanoscale PBNPs may exhibit superior enzyme activity and therapeutic potential. Mesoporous calcium–silicate nanoparticles (MCSNs) represent novel biocarriers with exceptional capabilities for carrying and continuously releasing various metal ions and chemical drugs (Leng et al 2020; Duan et al 2021). If PBNPs are incorporated into this carrier, it can prevent the oxidation of iron ions, enhance drug stability, improve drug bioavailability, and enhance treatment safety.…”
Section: Introductionmentioning
confidence: 99%